The Supreme Court and election law : judging equality from Baker v. Carr to Bush v. Gore - Hasen, Richard L. (New York University Press, 2003)
In the first comprehensive study of election law since the Supreme Court decided Bush v. Gore, Richard L. Hasen rethinks the Court's role in regulating elections. Drawing on the case files of the Warren, Burger, and Rehnquist courts, Hasen roots the Court's intervention in political process cases to the landmark 1962 case, Baker v. Carr. The case opened the courts to a variety of election law disputes, to the point that the courts now control and direct major aspects of the American electoral process. The Supreme Court does have a crucial role to play in protecting a socially constructed "cor.